Impact of Climate Change on Increasing Land Surface Temperature in Indonesia: A literature review - Latue, Philia Christi; Karuna, Joan Ria; Rakuasa, Heinrich; Pakniany, Yamres (Yayasan Adra Karima Hubbi, 2024)
This research explores the impact of climate change on increasing land surface temperature (LST) in Indonesia, which has shown a significant upward trend in recent decades. Using a systematic literature review, the research analyzed 50 relevant studies, identifying factors such as deforestation, urbanization, and greenhouse gas emissions as the main causes of increased LST. The research also highlights the serious implications of temperature change on agriculture, public health and water resources, which could lead to food insecurity and increased health risks. In addition, the research emphasizes the importance of understanding public attitudes and beliefs towards climate change to formulate effective policies. With an interdisciplinary approach, the results of this research aim to provide insights for policymakers and stakeholders in developing sustainable mitigation strategies, as well as increasing community resilience to the impacts of climate change in Indonesia.